Nuanced Archival Triangulation (NAT) - Seth Knievel (The International Journal of Information, Diversity, & Inclusion)
This article presents an innovative method for researching quotidian photography, particularly Real Photo Postcards (RPPC), by combining performance studies and archival sciences with oral narrative. The Nuanced Archival Triangulation (NAT) method culminates evidence from public records, newspapers, and local and non-traditional archival repositories with living family stories, resulting in a more nuanced approach to understanding people featured in visual archives. The NAT method extends and adapts Hulme’s methodology for researching textual archives of queer defendants in the United Kingdom in the early 20th century while also including Pennavaria’s genealogical methods that involve the family in historical research. The NAT methodology is comprised of four steps. Step one begins with examining traditional genealogical records of the person studied from the RPPC via Ancestry.com. Next, newspaper archives are accessed to uncover information about the individual’s social life to contextualize the biographical information found in step one. Then, guerilla research is used to locate non-traditional, undigitized evidence related to the studied person. And finally, that person’s family is contacted to solicit personal artifacts and family stories that illuminate the person’s lived story to share agency with the living relatives of the primary RPPC subject. This paper employs the NAT method in a case study centering on an RPPC of Dale Smith and Alvin Ruddick, two Navy sailors who served in WWII. By locating relevant biographical evidence, speculation about the subjects' sexual identities is investigated in the RPPC. This paper concludes by discussing how the NAT methodology can amplify marginalized communities' visual archives.